Strategic Physiognomy and its Impact on Organizational Prosperity : An Analytical Research in the State Company for Electrical and Electronic Industries - MOHAMMED, REYAM KASIM; SAAED, HADEEL KADHIM (The journal of contemporary issues in business and government, 2021)
The main objective of the research is to investigate the relationship and influence between strategic physiognomy and organizational prosperity in the General Company for Electrical and Electronic Industries and to identify the nature and pattern of thinking prevailing among the leadership levels in the concerned company in order to identify appropriate procedures and practices that work to consolidate the culture of strategic physiognomy and direct it towards achieving prosperity organizational , data were collected from ( 166 responder represent) late sample intentional from the middle and senior management and analysis of data Od ft statistical programs (SPSS, AMOS) Through the adoption of appropriate statistical methods . The results showed the health of relationships link and influence on the level of key variables and sub - dimensional, indicating the essential role of discernment and strategic of to achieve prosperity organization in the company